Hydrophilic materials based on hydrogel polymers for enrichment of glycopeptides from serum of colorectal cancer patients - Zhang, Xiqian; Wang, Danni; Shao, Jiahui; Mao, Haijiao; Ding, Chuan‐Fan; Yan, Yinghua (Journal of separation science, 2024)
In this work, a composite hydrogel material consisting of chitosan‐based composite hydrogel was prepared by a simple and rapid synthetic method and will be named three‐dimensional (3D)‐IL‐COF‐1@CS hydrogel. Possessing a stable 3D network structure and outstanding hydrophilicity, the novel hydrogel is capable of capturing glycopeptides. The 3D‐IL‐COF‐1@CS hydrogel showed good sensitivity (0.1 fmol/µL) and selectivity (1:2000). In addition, 19 glycopeptides were captured in standard samples. In the analysis of human serum, 148 glycopeptides assigned to 72 glycoproteins were assayed in the serum of normal individuals, and 245 glycopeptides corresponding to 100 glycoproteins were found in the serum of colorectal cancer (CRC) patients. More importantly, several functional programs based on Gene Ontology analysis supported molecular biological processes that may be relevant to the pathogenesis of CRC, including aging, fibrinogen complex, and arylesterase activity. The low cost, simplicity, rapid synthesis, and good enrichment performance have a great future in glycoproteomics analysis and related diseases.